Resilience after stroke and its correlation with functional independence - Heltty, Heltty; Zahalim, Zahalim (Universitas Airlangga, 2023)
Introduction: Resilience involves the ability to adapt to the conditions of disability experienced by post-stroke patients. The purpose of this study was to investigate the resilience of post-stroke patients and determine the relationship with the patient's functional ability. Methods: This research was a cross-sectional study that included 122 post-stroke patient respondents who had undergone a stroke recovery phase for 5 - 8 weeks. Selection of the sample used simple random sampling method. Univariate analysis was used to describe the characteristics of each respondent. Bivariate analysis was carried out to determine the relationship between resilience and functional abilities of respondents, especially functional abilities related to activities of daily living. Results: The results of this study found that there was a significant relationship between resilience and functional ability of the respondents (p = 0.000; 95% CI). Conclusions: Respondents with a high level of resilience can make better use of their abilities so that they can increase their functional independence abilities. Thus, it can achieve a better quality of life improvement.